STATUS PEKERJAAN DAN PEMBERIAN AIR SUSU IBU (ASI) PADA IBU DI WILAYAH PERKOTAAN INDONESIA - Monica Dara Delia Suja (SCIENTIA JOURNAL, 2022)
To reduce infant morbidity and mortality, since 2001 the World Health Organization (WHO) has recommended exclusive breastfeeding for infants for at least 6 months. This study aims to identify the relationship between the mother's employment status and the provision of breast milk (ASI) to working mothers who live in urban areas. This research is a quantitative study with a cross-sectional research design using data from the Indonesia Family Life Survey 5. The sample in this study is mothers aged 15-49 who work, have children aged 2 years and live in urban areas. The sample size in this study was 340 respondents. Employment status is divided into entrepreneurs, government employees, private employees, and casual workers, while breastfeeding is divided into less than 2 years and for 2 years. Analysis using chi-square and logistic regression. For working mothers in urban areas, the percentage of mothers who gave breast milk for less than 2 years was 68.82%, while mothers who gave breast milk for 2 years was 31.18%. The employment status of mothers who live in urban areas is mostly private employees (42.06%) and entrepreneurs (34.41%). Employment status with a percentage of breastfeeding less than 2 years are government employees (77.78%) and private employees (75.52%). There is a relationship between the mother's employment status and breastfeeding to working mothers who live in urban areas. Mothers who have employment status as entrepreneurs are 1.85 times more likely (95% CI 1.09 – 3.17) to provide breastfeeding for 2 years compared to mothers who work as private employees. Support to provide breastfeeding rights for women workers must be increased. Forms of workplace support can be provided by providing lactation rooms, daycare or creating a conducive work environment for breastfeeding mothers.